Sensing of Liver‐Derived Nicotinamide by Intestinal Group 2 Innate Lymphoid Cells Links Liver Cirrhosis and Ulcerative Colitis Susceptibility - Jing Shen; Zhen Li; Xiaoyu Liu; Mengqi Zheng; Peng Zhang; Yatai Chen; Qiuheng Tian; Wenyu Tian; Guanjun Kou; Yanyan Cui; Bowen Xu; Yunjiao Zhai; et al. (Advanced Science)
Abstract The correlation between liver disease and the progression of ulcerative colitis (UC) has remained elusive. In this study, it demonstrates that liver injury is intricately linked to the heightened severity of UC in patients, and causes more profound intestinal damage during DSS‐induced colitis in mice. Metabolomics analysis of plasma from liver cirrhosis patients shows liver injury compromising nicotinamide supply for NAD+ biosynthesis in the intestine. Subsequent investigation identifies intestinal group 2 innate lymphoid cells (ILC2s) are responsible for liver injury‐exacerbated colitis. Reconstitution of ILC2s or the restoration of NAD+ metabolism proves effective in relieving liver injury‐aggravated experimental colitis. Mechanistically, the NAD+ salvage pathway regulates gut ILC2s in a cell‐intrinsic manner by supporting the generation of succinate, which fuels the electron transport chain to sustaining ILC2s function. This research deepens the understanding of cellular and molecular mechanisms in liver disease‐UC interplay, identifying a metabolic target for innovative treatments in liver injury‐complicated colitis.